P74 British asthma guideline revision does affect prescribing patterns in children. (16th November 2010) - Elkout, H; McLay, J S; Simpson, C R; Helms, P J
Abstract : Background: Although audits of prescribing practice referenced to the British asthma management guidelines have been reported little is known on the impact of guideline revisions. Concerns about the use of high dose inhaled corticosteroids (ICS) in children, implicit in earlier adult oriented guidelines, has resulted in the promotion of add on therapy with long acting beta agonist (LABA) and/or leukotriene receptor antagonist (LTRA) and advice on age appropriate doses of short courses of oral corticosteroids (OCS) for exacerbations. Methods: Prescribing of asthma medication for children 0–18 years from 46 Scottish General Practices contributing to the Practice Team Information (PTI) database was assessed before (2001–2) and after the 2003 BTS/SIGN guideline revision 1 (2005–6). PTI represents the rural/urban and socioeconomic make up of the whole Scottish population and includes 155 230 children in the 0–18 year age group (7.2–7.8% with at least one prescription for an asthma medication per year). Results: In those children prescribed at least one asthma medication in each year of study, ICS at high dose (>400 μg beclometasone equivalent) decreased from 16.3% in 2001–2 to 11.7% in 2005–6 (p<0.001). This was accompanied by an increase in the prescribing of add-on therapy (LABA and/or LTRA) from 15.0% in 2001–2 to 26.2% in 2005–6. Prescribing of short courses (5–7 days) of OCS increased most prominently in children aged <5 years (from 6% in 2001–2 to 16% in 2005–6, p<0.001) for children at all treatment steps including those prescribed short acting beta agonist only. Only 27 children were prescribed LABA without concurrent ICS and of the 710 children prescribed LABA/ICS combination, 176 (25%) had not been prescribed ICS in the previous year. Conclusions: Revisions of the BTS/SIGN guidelines do modify prescribing practice in children. The greater use of LABA, LTRA and reduction in ICS dose has been accompanied by a greater use of OCS that may reflect poorer control of acute episodes or a lower threshold and greater confidence by prescribers in the use of OCS.